Squaring the Virtuous Circle: Exploring the Potential of the 'Five Cs' - Butcher, John (Blackwell Publishing, 2015)
During his May 2014 visit to Australia Pascal Lamy, former Director General of the World Trade Organization, urged 'public institutions, civil society, and global businesses' to forge 'creative coalitions' for the purpose of engaging constructively and positively with the complex problems standing in the way of achieving social and economic sustainability. Lamy's visit was but the first of several occasions during 2014 in which intense public discussion erupted about the need for government, business, and civil society to pool their capacities in boundary-spanning efforts to address complex policy problems. This article investigates whether the public discussion portends a heightened policy focus on the 'five Cs': co-production, co-design, corporate social responsibility, collective impact, and Lamy's creative coalitions.